Plasmas Maintained by Microwave Fields and Specifically by Surface Waves - Moisan, M.; Ricard, A. (Plasmas Afterglows with N\(_2\) for Surface Treatments New Results, 2024)
Plasmas driven by electromagnetic surface waves can create long columns of plasma under an unrivalled range of operating conditions, which are the frequency of the wave (a few MHz to 10 GHz), the internal radius of the discharge tube (0.5 mm to 150 mm demonstrated), and the density and nature of the carrier gas (mTorr range to atmospheric pressure with both atomic and molecular gases). These plasmas are produced by coupling power to radiofrequency (RF) and microwave (MW > 100 MHz) generators with no significant loss of power while remaining perfectly stable and reproducible. They are achieved using an electromagnetic field applicator, the axial dimension of which can be small compared with the long plasma columns that can be obtained (4 m 50 long demonstrated) in low-permittivity, low-loss dielectric discharge tubes (e.g., Pyrex brands, fused silica). Two main field applicators have been developed to efficiently generate SW plasmas, namely the surfatron and the surfaguide. The advantage of using them here is that they work in such a way as to obtain radial distributions of electron density and excited species that tend to flatten out, unlike a Bessel-type distribution with DC discharges, while at the same time, the discharges are much less contaminated due to the absence of electrodes compared with DC discharges. Argon gas has been mainly used to investigate through optical spectroscopy the radial distribution of radiative and metastable excited species of these SW-sustained discharges as a function of operating conditions. The N2-xO2 gas mixture with x=0-20% was also studied, as a SW discharge itself and for its remarkably long afterglows (early and late (without ions)). Several microwave plasmas sources are described from low-pressure Ar plasmas: surfatron and surfaguide cavity up to atmospheric gas pressure Ar plasmas as TIA/TIAGO torches. In atmospheric gas Ar plasma, the LTE was nearly reached in the TIAGO rod torch with 5000K at the dart origin quickly decreasing to 2500K in the plume at 12.5 cm. The TIA torch with an exit nozzle of 1 mm was out LTE but with a high temperature of (3-4)103K over 15 cm. The present chapter is marked by the contribution in progress of Michel Moisan, conducing to an enrichment of the previous chapter 8 published in 2021-23 [1].